EMPATI TERHADAP KINERJA GURU SEKOLAH LUAR BIASA - IRIANI INDRI HAPSARI; TIARA ARMAYANTI (Journal of Research and Measurement in Psychology, 2017)
This reasearch aims to find the effect of empathy toward teacher’s performance in School for disabled children. This reasearch used quantitative method. A Questionnaire of Cognitive and Affective Emphaty (QCAE) was adopted and used to measure the empathy, and teacher’s performance measured by using instrument that developed from teacher’s performance appraisal. Purposive sampling technique was used for the sampling technique. The participan of this reasearch is 81 teachers from school for disabled children in East Jakarta. The result if this reasearch showed that Fhit= 10,214 > Ft = 3,94 ; p = 0,002 < α = 0,05 which means there’s a significant effect of emphaty toward teacher’s performance in school of disabled children which is 11,4%.